Prolonged extracorporeal preservation and evaluation of human lungs with portable normothermic ex vivo perfusion. Issue 3 (19th February 2020) - Spratt, John R.; Mattison, Lars M.; Kerns, Natalie K.; Huddleston, Stephen J.; Meyer, Linette; Iles, Tinen L.; Loor, Gabriel; Iaizzo, Paul A.
Abstract: Many lung donor offers are refused despite increasing demand. Portable normothermic ex vivo lung perfusion (EVLP) could increase donor yield by monitoring and reconditioning extended criteria donor (ECD) lungs. We report its use in human lungs declined for clinical transplantation. Ten sets of such lungs were procured from brain‐dead donors and underwent 24 hours of normothermic EVLP using a perfusate based on donor whole blood. Hemodynamic and ventilatory data and P:F ratios were measured. Advanced donor age and borderline oxygenation (donor mean P:F 228 ± 73) were the most commonly cited reasons for refusal for transplantation. There was no significant worsening of pulmonary hemodynamics or compliance or significant P:F decline during preservation in the overall cohort. Mean P:F ratio in the overall cohort was 315 ± 88 mm Hg after 24 hours EVLP. At EVLP termination 5/10 lung blocks met standard EVLP thresholds for acceptability for transplant. Eventual EVLP performance was poorly predicted by donor P:F ratio but well predicted by data gathered early in EVLP. Portable normothermic EVLP is useful for transportation, monitoring, and reconditioning of ECD lungs. Early EVLP measurements are more effective than preprocurement donor P:F in predicting eventual allograft performance. We advocate an aggressive strategy of evaluation of ECD lungs using blood‐based EVLP.